What matters for regional industrial dynamics in a transitional economy?. Issue 1 (2nd January 2017) - He, Canfei; Zhu, Shengjun; Yang, Xin
ABSTRACT: Recent evolutionary economic geography (EEG) studies have argued that regional diversification emerges as a path-dependent process, as a region often branches into related industries, whereas unrelated industries have a high probability of exiting the region. Based on a firm-level dataset of China's manufacturing industries during 1998–2008, this paper examines the entry and exit of four-digit industries at the prefectural level, and shows that Chinese regional industrial development is a path-dependent process that is also affected by industry characteristics and the institutional framework. The results imply that EEG would profit from incorporating insights on institutional change and industry characteristics in explanations of regional industrial evolution.